Fuzzy control systems - Vukadinovic, Dinko (Mathematics research developments series., 2012)
Photo of Sendai Rinkai Railway Nishiko line by Alt_Winmaerik (Own work) [CC-BY-SA-3.0 (www.creativecommons. orglicensesby-sa3.o)], via Wikimedia Commons Photo of arc welding robot by Orange Indus (FANUC Robotics Deutschland) [CC-BY-SA-3.0 (www.creativecommons orghcensesby-sa3.o)], via Wikimedia Commons Cover design: Sharon Carty.